The Role of Organizational Ethics and Human Resource Social Responsibility in Enhancing Employee Commitment (Pusat Riset dan Inovasi Nasional, 2025)
A Employee commitment has become a critical concern for organizations operating in increasingly competitive and dynamic business environments. Beyond economic incentives, contemporary organizations are required to strengthen ethical values and social responsibility in human resource management to sustain long-term employment relationships. Organizational ethics and human resource social responsibility (HR-SR) have emerged as strategic dimensions that shape employees’ perceptions, attitudes, and psychological attachment to the organization. However, existing studies tend to examine these constructs separately, with limited efforts to synthesize their integrated role in enhancing employee commitment. This study aims to address this gap by conducting a comprehensive literature review on the role of organizational ethics and human resource social responsibility in fostering employee commitment.